Identification of pathogen-specific genes through microarray analysis of pathogenic and commensal Neisseria species. - Stabler, R; Marsden, G; Witney, A; Li, Y; Bentley, S; Tang, C; Hinds, J (2005)
The release of the complete genome sequences of Neisseria meningitidis MC58 and Z2491 along with access to the sequences of N. meningitidis FAM18 and Neisseria gonorrhoeae FA1090 allowed the construction of a pan-Neisseria microarray, with every gene in all four genomes represented. The microarray was used to analyse a selection of strains including all N. meningitidis serogroups and commensal Neisseria species. For each strain, genes were defined as present, divergent or absent using gack analysis software. Comparison of the strains identified genes that were conserved within N. meningitidis serogroup B strains but absent from all commensal strains tested, consisting of mainly virulence-associated genes and transmissible elements. The microarray was able to distinguish between pilin genes, pilC orthologues and serogroup-specific capsule biosynthetic genes, and to identify dam and drg genotypes. Previously described N. meningitidis genes involved in iron response, adherence to epithelial cells, and pathogenicity were compared to the microarray analysis. The microarray data correlated with other genetic typing methods and were able to predict genotypes for uncharacterized strains and thus offer the potential for a rapid typing method. The subset of pathogen-specific genes identified represents potential drug or vaccine targets that would not eliminate commensal neisseriae and the associated naturally acquired immunity.